Ureaplasma parvum genotype, combined vaginal colonisation with Candida albicans, and spontaneous preterm birth in an Australian cohort of pregnant women. Issue 1 (December 2016) - Payne, Matthew; Ireland, Demelza; Watts, Rory; Nathan, Elizabeth; Furfaro, Lucy; Kemp, Matthew; Keelan, Jeffrey; Newnham, John
Abstract Background Detection ofUreaplasma, Mycoplasma andCandida spp. in the vagina during pregnancy has previously been associated with preterm birth (PTB). However, the prevalence of these microorganisms and the associated obstetric risks (likely to be population-specific) have not been determined in Australian women; furthermore, in the case ofUreaplasma spp., very few studies have attempted characterisation at the species level and none have examined genotype/serovar status to further refine risk assessment. Methods In order to address these issues we sampled the vaginal fluid of 191 pregnant Australian women at three time points in pregnancy. Culture methods were used for detection ofUreaplasma spp. andCandida spp., and real-time PCR was used for speciation ofU. parvum andU. urealyticum, non-albicansCandida spp., Mycoplasma hominis andMycoplasma genitalium . High-resolution melt PCR was used to genotypeU. parvum . Data on various lifestyle factors (including sex during pregnancy and smoking), antimicrobial use and pregnancy outcome were collected on all participants. Chi-square tests were used to assess the association of vaginal microorganisms with PTB. Results Detection ofUreaplasma spp. was higher among spontaneous PTB cases, specifically in the presence ofU. parvum [77 % preterm (95 % confidence interval (CI) 50–100 %) vs. 36 % term (CI: 29–43 %), p  = 0.004], but notU. urealyticum . The association with PTB strengthened whenU. parvum genotype SV6 was detected (54 % preterm (CI: 22–85 %) vs. 15 % term (CI: 10–20 %), p  = 0.002); this genotype was also present in 80 % (4/5) of cases of PTB <34 weeks gestation. When present withCandida albicans in the same sample, the association with PTB remained strong for bothU. parvum [46 % preterm (CI: 15–78 %) vs. 13 % term (CI: 8–18 %), p  = 0.005] andU. parvum genotype SV6 [39 % preterm (CI: 8–69 %) vs. 7 % term (CI: 3–11 %), p  = 0.003]. With the exception ofCandida glabrata, vaginal colonisation status for all organisms was stable throughout pregnancy. Smoking significantly increased the likelihood of detection of all target organisms. Conclusions These data suggest that the presence of different species and serovars ofUreaplasma spp. in the vagina confers an increased risk of spontaneous PTB, findings which may be useful in risk assessment for identifying women who would benefit from antimicrobial treatment.